Injury and Illness in Marching Band and Color Guard Members and the Need for Athletic Trainers: A Critically Appraised Topic - Alissa C. Rhode (Bowling Green State University, 2017)
Purpose: To determine the prevalence, incidence, risk, rate, and type of injury and illness suffered by collegiate and high school marching band (MB) and color guard (CG) members and determine if there is a need for medical coverage. Methods: Articles were identified from: PubMed, CINAHL, MEDLINE, Physical Therapy and Sports Medicine Collection, ScienceDirect, and single-citation matching using search string, ["marching band" OR "color guard" OR "marching athlete" AND injury] from January 1990-to-October 2016, resulting in 141 articles. Following screening (title, abstract), six articles were reviewed. Four met these inclusion criteria: (1) peer-reviewed, cross-sectional studies, (2) high school or collegiate-aged members, (3) available abstract, (4) English language, (5) included prevalence, incidence, risk, rate, or type of musculoskeletal injury (MSI) and sudden illness (SI). Two reviewers assessed the level of evidence (LOE) and quality using the Oxford Center for Evidence-Based Medicine (2009) and STROBE instruments. Data of interest subjects, injury/illness prevalence/incidence and classification (descriptive statistics), and risk/rate of injury. Results: Four studies were evaluated (LOE=2b; STROBE 18.62±4.37 [based on a 36-point scale]). Pooled sample size was 2,272, in collegiate (n=3) and high school (n=1) aged members with MB only (n=1), MB and CG (n=2), and unidentified members (n=1) over different season lengths. All studies agree MB and CG are strenuous activities with significant potential for lower extremity (LE) MSI as it was between 27%-87.7% of reported injuries (n=3); illnesses were 22-34%. Conclusions: Results strongly indicate that MB and CG are likely to sustain LE MSI and the nature of the activity predisposes members to certain types. Thus athletic trainers should be present to provide injury prevention and manage MSI and SI when they arise.